1.
[tex]A) \ 2x+5 = 2\cdot3 + 5 =6+5 = 11\\\\B) \ x-7 = 2-7 = -5\\\\C) \ 3x+4 = 3\cdot(-2)+4 = -6+4 = -2\\\\D) \ x^{2}+1 = 4^{2} + 1 = 16+1 = 17\\\\E) \ x+y = 2+(-4) = 2-4 = -2\\\\F) \ 7-xy = 7 - 3\cdot(-2) = 7+6 = 13\\\\G) \ x(3-y) = 3(3-5) = 3\cdot(-2) = -6[/tex]
[tex]H) \ 4-6x = 4 - 6\cdot(-3) = 4 +18 = 22\\\\I) \ 4x-2y = 4\cdot(-3)-2\cdot(-4) = -12+8 = -4\\\\K) \ x(x-3) = -11(-11-3) = -11\cdot(-14)= 154\\\\L) \ x^{2}-4x+12 = (\frac{1}{2})^{2}-4\cdot\frac{1}{2}+12 = \frac{1}{4}-2+12 = \frac{1}{4}+10 = 10\frac{1}{4}\\\\M) \ x^{3}-x^{2} = (-1)^{3}-(-1)^{2} = -1 -1 = -2[/tex]